The glory and the dream a narrative history of America, 1932-1972 - Manchester, William 1922-2004 (Little, 1974)
A popular history of the United States which encompasses politics, military history, economics, the lively arts, science, fads, fashion, social changes, sexual mores, and communications, with brief biographies of notable Americans--Cover.